Basic Coding Block Mentorship for IT School Teachers at Insan Teladan Cileunyi, Bandung District - Erwin Susanto; Sumaryo, Sony; Dwibawa, Ig Prasetya (Journal of Community Practice and Social Welfare, 2024)
Teachers in schools need to understand the development of technology in the current era of Industry 4.0. With this background, education about technology and its advancements, particularly in the fields of coding and robotics, is essential so that teachers (who are then expected to transfer their knowledge to students) can better understand the importance of learning programming (coding) and robotics in the latest technological developments. In practice, teachers at Insan Teladan Integrated Islamic School (IT) are constantly seeking suitable methods and tools to realize the school's mission, which is technology-oriented. Here is where community service through mentoring activities by Telkom University lecturers, Electrical Engineering undergraduate program, plays a role. The goal is to enhance teachers' understanding of the use of information technology (coding) and robotics to support the teaching-learning process. Based on feedback obtained from the target community (teachers) who filled out questionnaires, it can be concluded that 91% of the target community agrees or strongly agrees that this activity meets their needs.